Il giudice (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The Italian Constitution designs a model of the fundamental rights defence based on the clear roles of the lawmaker, the judge and the constitutional Court. Many alterations are occurring in this model, some caused by the action of the EUJC e the ECHR Court. Biolaw is an area where the phenomenon in adverted strongly. Entropy is a useful model to understand it.
Keywords: Fundamental rights; role of the jurisdiction; role of lawmaker; role of the constitutional Court; entropy